Neptune Project: Transforming Personal Narrative Into Political Statement in an Autobiographical Play - Boitcova, Vera (Taideyliopiston Teatterikorkeakoulu, 2023)
This thesis explores the ways in which personal narratives in dramaturgy can be read as political statements on the example of creating and staging my autobiographical queer play Neptune over the course of two years (March 2021-March 2023). My research questions include: - What circumstances can evoke a creative desire to transform personal into political through art mediums? To what extent performance art can be effective as a tool to convey political messages? - How to convey political messages through personal narratives in dramaturgy\playwriting? What makes a narrative political and what can be defined as a political narrative? What does ‘being political’ mean specifically for a queer artist\dramaturge? - What methodology, aesthetical, directorial and acting choices can be made to further enhance and underline political message of a documentary narrative, specifically in queer context? These questions will be examined in a detailed account of writing my own autobiographical play Neptune in the year of war and strengthening of oppression in Russia, and subsequent staging of this play. My play had three distinct layers: meta-level (where the narrator talked about her recent political experiences in the year 2022), memory level (subjective memories of a lost love), and fictional level (different characters acting in thematically-relevant vignettes). Therefore, I want my thesis to be reflective of the same structure: it will have three main chapters - Meta, Memory, and Fiction – with the overall reflection at the end. Overall aim of this thesis is to trace the process of creating an autobiographical play from its creative conception (and reasons behind it) to turning it into a theatre production, and by doing so, to examine if it succeeded in its initial goal of conveying a certain political message, and if so, how this result was achieved.
Keywords: queer studies; political art; autobiographical approach; comparative dramaturgy